Simulated Grocery Store, Restaurant, and Kitchen: A Practical Approach to Teaching Clinical Nutrition - Kimberly Zoberi; James Deckert (Association of American Medical Colleges, 2007)
Abstract This workshop consists of multiple nutrition teaching stations. Each station has a question posted and also has several products for the student to examine or compare. For example, there may be various kinds of canned fish or boxes of different brands of snack crackers. The students rotate through the stations, examining products, reading nutrition labels, and answering questions regarding each station. During this process, the students become aware of their strengths and deficits regarding these topics. After the students finish rotating through the stations, each topic is addressed with an interactive presentation. The entire workshop takes about 90 minutes; approximately 15 minutes is spent rotating through the nine stations, and the rest of the time is used for the presentation and discussion of each topic. However, the timing of this workshop can easily be adjusted since stations can be added or eliminated to fit in the time allowed. Evidence-based resources are cited, and students are encouraged to share their experiences or opinions on the topic. Pre- and postworkshop knowledge evaluations have shown a significant increase in the number of items correctly answered by students. Evaluations have also shown that students appreciate having real products to examine and that some students may have deeply held opinions about certain topics, including alcohol and organic foods. We emphasize the sources used and encourage students to apply this knowledge as appropriate to a specific clinical situation.